2014
DOI: 10.1088/1748-0221/9/02/c02030
|View full text |Cite
|
Sign up to set email alerts
|

A polarization-based Thomson scattering technique for burning plasmas

Abstract: The traditional Thomson scattering diagnostic is based on measurement of the wavelength spectrum of scattered light, where electron temperature measurements are inferred from thermal broadening of the scattered laser light. At sufficiently high temperatures, especially those predicted for ITER and other burning plasmas, relativistic effects cause a change in the polarization state of the scattered photons. The resulting depolarization of the scattered light is temperature dependent and has been proposed elsewh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…The problem of the optimization of the polarization state of the input laser beam for polarimetric TS in the conditions of ITER has already been investigated by calculating the depolarization of TS radiation integrated over the entire wavelength spectrum [1,3,4]. These calculations have shown that for the above backward-like geometry the depolarization of the scattering radiation is maximized by using an input laser beam with circular polarization.…”
Section: Polarimetric Scattering On the Iter Core Ts Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…The problem of the optimization of the polarization state of the input laser beam for polarimetric TS in the conditions of ITER has already been investigated by calculating the depolarization of TS radiation integrated over the entire wavelength spectrum [1,3,4]. These calculations have shown that for the above backward-like geometry the depolarization of the scattering radiation is maximized by using an input laser beam with circular polarization.…”
Section: Polarimetric Scattering On the Iter Core Ts Systemmentioning
confidence: 99%
“…In order to obtain a quantitative estimate it is necessary to calculate the expected measurement error on a set of suitably chosen 2016 JINST 11 C01071 polarimetric signals and propagate them to the final values of T e and n e . To this purpose it is important to consider that the polarization state of the TS radiation is frequency dependent and therefore when the spectral range of the detected radiation is limited as in our case, the signal in a polarimetric channel must be calculated using the spectral TS Mueller matrix M(ω, θ, T e ) whose elements are functions of the frequency ω of the scattered radiation [2][3][4].…”
Section: Polarimetric Scattering On the Iter Core Ts Systemmentioning
confidence: 99%
See 3 more Smart Citations